Boca Junior´s Sport City: traces of an unfinished project in Buenos Aires, Argentina - Santaló, Claudia Berta (2023)
This article searches about those places that have been perpetuated, not by an official recognition, but under the popular memory and however they actually conserve a high symbolic value for a determined part of the community. Such is the case of the Ciudad Deportiva de Boca settled in the south coast of Buenos Aires, Argentina. In the 60 of the XX century, it wasnot only a place for popular recreation and social affairs but also a project and a plural dream around one of the most important football club of this country. From that dreamed Ciudad Deportiva, nowadays only remains ruins and a private project of real state development. The changes in this place along the time show the constant and unavoidable relation between the urban spaces and the political processes.